1998
DOI: 10.1097/00005537-199803000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Snorers and Sleep Apnoics Have Abnormal Vascular Reactions of the Soft Palatal Mucosa on Afferent Nerve Stimulation

Abstract: A local disturbance in the afferent nerves involved in the reflexogenic dilation of the upper airways (UAs) could contribute to the increased collapsibility seen in patients with obstructive sleep apnea (OSA). Laser Doppler perfusion monitoring, combined with electrical stimulation, is a method for investigating the afferent nerve regulation of the microcirculation. It was used in the mucosa of the soft palate in 35 patients with various degrees of UA obstruction and in 13 control subjects, all nonsmoking men.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 24 publications
2
29
0
6
Order By: Relevance
“…In agreement with this phenomenon, an interesting finding of the present study was that the OSAS patients with greater longest snoring time, average snoring episode duration, and relative snoring time on polysomnography tended to have impaired sensation of the soft palate. This finding was also consistent with previous studies [6,7,[15][16][17]. In spite of the conception that the subocclusive stage in snoring precedes the development of OSA [21], there was a broad spectrum ranging from mild to severe snorers among OSAS subjects.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with this phenomenon, an interesting finding of the present study was that the OSAS patients with greater longest snoring time, average snoring episode duration, and relative snoring time on polysomnography tended to have impaired sensation of the soft palate. This finding was also consistent with previous studies [6,7,[15][16][17]. In spite of the conception that the subocclusive stage in snoring precedes the development of OSA [21], there was a broad spectrum ranging from mild to severe snorers among OSAS subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Several authors [9][10][11]15,19 provided evidence for local neurogenic lesions in OSA. Most of these authors hypothesized that snoring was responsible for the histologic alterations reported.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism is believed to be local neurogenic lesions in the oropharynx caused by the low-frequency vibration of habitual snoring in OSA 11,12 .…”
mentioning
confidence: 99%
“…These episodes are of short duration, about four breaths, and present negative intrathoracic pressure increases. Another interesting difference from OSAS is that UARS patients do not present neuropathological lesions in the upper airway (Friberg 1998;Guilleminault 2002a;Boyd 2004), which could explain why these patients tend to respond more rapidly to treatment and do not develop OSAS over the long-term. Early studies did not seem to reveal differences in sleep architecture between UARS and OSAS .…”
Section: Pathophysiologymentioning
confidence: 99%